Penggunaan Model Pembelajaran Quantum Disertai LKPD IPA Berbasis Multirepresentasi untuk Mengukur Hasil Belajar Peserta Didik Kelas VIII - Pramdesti Aprilina; I Ketut Mahardika; Iwan Wicaksono (Universitas Tadulako, 2023)
Science learning aims to provide opportunities for students to cultivate curiosity and seek answers naturally. However, its obstacle is that the learning models selection which is less varied and innovative so that affect student learning outcomes. An alternative solution to overcome these problems is the use of Quantum learning model which creates fun learning atmosphere. The aim of this study is to examine the effect of using Quantum learning model with multi-representation-based science worksheets on grade VIII students learning outcomes. The research design used quasi-experimental form of non-equivalent control group design. The research subjects were grade VIII students of SMPN 03 Bondowoso consisted of 7 classes with 2 classes as the research sample totaling 64 students. The sampling technique used was cluster random sampling. Data collection techniques were through pre-test, post-test, observation, interviews, and documentation. The data were analyzed using statistical tests through normality test, homogeneity test, and independent sample t-test. The experimental class post-test value shows higher than control class. In addition, data analysis shows the data value sig.(2-tailed) of 0.049 < 0.05 which means there are differences in experimental class and the control class learning outcomes. Thus, the Quantum learning model has significant effect on student learning outcomes.